Orchards from Grapes of Wrath - Thomas Hart Benton (Artist):::Creator::::::::::::
Orchards in spring from The Grapes of Wrath, v.2, p.425, illustrated edition. Chapter 25 heading, Steinbeck describes the orchards of California. Thomas Hart Benton, a native of eastern Oklahoma, was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "The spring is beautiful in California. Valleys in which the fruit blossoms are fragrant pink and white waters in a shallow sea."